2019
DOI: 10.1021/jacs.9b09639
|View full text |Cite
|
Sign up to set email alerts
|

Superacid-Mediated Functionalization of Hydroxylated Cucurbit[n]urils

Abstract: Herein we report a facile transformation of hydroxylated cucurbit[n]uril (CB[n], n = 6 and 7) to other functionality-conjugated CB[n]s by nucleophilic substitution of the hydroxyl group with a wide range of nitriles and alcohols. The reaction proceeds efficiently via generation of a superelectrophilic carbocation on the CB framework from hydroxylated CB[n]s under superacidic conditions. One of the resulting CB[n] derivatives with reactive functionality, monocarboxylated CB[7], is efficiently conjugated to an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…their crystal structure [45] . e) Detection of ADA‐BSA using CB[7]‐HRP‐catalyzed oxidation of luminol by H 2 O 2 [48] . The crystal data in (a–d) are deposited in the Protein Data Bank (PDB).…”
Section: Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…their crystal structure [45] . e) Detection of ADA‐BSA using CB[7]‐HRP‐catalyzed oxidation of luminol by H 2 O 2 [48] . The crystal data in (a–d) are deposited in the Protein Data Bank (PDB).…”
Section: Proteinsmentioning
confidence: 99%
“…For example, the chemical modification of hydroxylated CBs has been readily realized through nucleophilic substitution under acidic conditions (Figure 5 e). [48] To explore the practicability of protein labeling and detection, one of the transformation products, monocarboxylated CB[7], was conjugated with horseradish peroxidase (HRP) via amide condensation. Consequently, the adamantane‐grafted bovine serum albumin (ADA‐BSA) was visually detected with assistance of CB[7]‐grafted HRP (CB[7]‐HRP), which was jointly attributed to the tight host–guest association and the amplified chemiluminescent signal output triggered by H 2 O 2 .…”
Section: Proteinsmentioning
confidence: 99%
“…51 The Kim group recently demonstrated a superacid-mediated conversion of the hydroxyl group on Q[n]s (n = 6 and 7) to yield other important functional groups in high yields. 52 Additionally, they found that the resulting substituted Q[n] can be readily conjugated to an enzyme to afford a Q[n]-conjugated enzyme which is useful in protein blotting assays. 53 Other groups also have made significant progress towards functionalizing Q[n] homologues.…”
Section: Synthesis Of Substituted Q[n]smentioning
confidence: 99%
“…[45] e) Detection of ADA-BSA using CB [7]-HRP-catalyzed oxidation of luminol by H 2 O 2 . [48] The crystal data in (a-d) are deposited in the Protein Data Bank (PDB).…”
Section: Cb-mediated Protein Structuresmentioning
confidence: 99%
“…[47] In turn, the photophysical performance of the included chromophoric guest molecules could be considerably enhanced by the mutual cooperation between CBs and proteins.M eanwhile, the emergence of chemically modified CBs has opened up great opportunities to widen the biological applications of multicomponent CB-protein assemblies.F or example,t he chemical modification of hydroxylated CBs has been readily realized through nucleophilic substitution under acidic conditions (Figure 5e). [48] To explore the practicability of protein labeling and detection, one of the transformation products, monocarboxylated CB [7],w as conjugated with horseradish peroxidase (HRP) via amide condensation. Consequently,the adamantane-grafted bovine serum albumin (ADA-BSA) was visually detected with assistance of CB [7]-grafted HRP (CB [7]-HRP), which was jointly attributed to the tight hostguest association and the amplified chemiluminescent signal output triggered by H 2 O 2 .T his practical synthetic methodology can remove the roadblocks in the site-selective functionalization of the CB skeleton, which may allow the creation of al ibrary of biosensing platforms based on the chemically active CB derivatives.…”
Section: Angewandte Chemiementioning
confidence: 99%